Ethics in Extremis: Stoic Philosophy and the Theatre of Blood in Seneca’s Thyestes (SCHOLARS: Journal of Arts & Humanities, 2025)
This paper investigates the complex relationship between Stoic philosophy and the extreme violence depicted in Seneca’s play Thyestes, focusing on how Stoic virtue endures or collapses under intense moral and emotional pressure. Thyestes is often referred to as a "theatre of blood" due to its portrayal of revenge, fratricide, and cannibalism, which seem at odds with Stoic ideals like rationality, self-mastery, and apatheia. As both philosopher and dramatist, Seneca constructs a paradox: Stoic ethics, committed to reason and virtue, can resist the disintegration of moral order. This study examines Thyestes as a philosophical drama where Stoicism is tested under conditions of corruption, familial betrayal, and existential horror. It aims to explore how Stoic principles are enacted or undermined in the play, analyze the moral psychology of Atreus and Thyestes, and argue that Seneca uses tragedy to probe the limitations of philosophical doctrine. Drawing on the Stoic teachings of Chrysippus and Epictetus, and engaging with modern interpretations by A.A. Long, the paper situates Thyestes within a critical tradition that interrogates the practical viability of ethical systems. Using a qualitative method rooted in close literature and textual analysis, the paper bridges literary criticism and Stoic ethics. It addresses a scholarly gap by treating Thyestes not as detached rhetoric, but as an integral part of Seneca’s moral philosophy. The central argument is that the play dramatizes the inner tensions of Stoicism, particularly the conflict between reason and virtue, while forcing a confrontation with the fragility of morality in the blood-soaked world of Thyestes: a true theatre of ethics in extremis. Thyestes exposes the internal tensions and limitations of Stoic philosophy by dramatizing how reason and virtue struggle and ultimately falter amid extreme moral and emotional devastation.